2017
DOI: 10.1039/c6ib00245e
|View full text |Cite
|
Sign up to set email alerts
|

Local remodeling of synthetic extracellular matrix microenvironments by co-cultured endometrial epithelial and stromal cells enables long-term dynamic physiological function

Abstract: Mucosal barrier tissues, comprising a layer of tightly-bonded epithelial cells in intimate molecular communication with an underlying matrix-rich stroma containing fibroblasts and immune cells, are prominent targets for drugs against infection, chronic inflammation, and other disease processes. Although human in vitro models of such barriers are needed for mechanistic studies and drug development, differences in extracellular matrix (ECM) needs of epithelial and stromal cells hinder efforts to create such mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 92 publications
4
101
0
Order By: Relevance
“…Therefore, the local in-gel measurements may be a more accurate method to reveal unknown interactions in complex 3D systems. These proof-of-principle studies with cell lines demonstrate the potential for this approach for detailed hypothesis-driven mechanistic studies with primary cells, which produce cytokines and growth factors more abundantly than cell lines (35). …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, the local in-gel measurements may be a more accurate method to reveal unknown interactions in complex 3D systems. These proof-of-principle studies with cell lines demonstrate the potential for this approach for detailed hypothesis-driven mechanistic studies with primary cells, which produce cytokines and growth factors more abundantly than cell lines (35). …”
Section: Resultsmentioning
confidence: 92%
“…We previously observed that the PHSRN-K-RGD peptide enhanced epithelial and stromal behaviors (attachment to gels, epithelial monolayer properties) compared to the minimal peptide RGD (35). In those studies, epithelial cells were cultured on functionalized gels.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…EECs were grown to confluence, passaged, and seeded at a density of 4 x 10 5 cells/mL on 5 wt% GelMA hydrogels cast in Ibidi angiogenesis μ slides [35]. Cells were allowed to attach for 6 hours and then hydrogels were washed once with cell growth medium to remove any unattached cells.…”
Section: Epithelial Monolayer Formationmentioning
confidence: 99%